Tax Design in the Presence of Status-driven Secondary Poverty - Alessandro Balestrino (Public Finance Review, 2026)
The existence of the working poor is a well-recognised and worrisome phenomenon in contemporary Western societies. In this paper, it is argued that one of its causes is the prevalence of status-seeking behaviour among economic agents. Such behaviour can be seen as an evolutionary advantageous trait hard-wired in the agents’ brains; it has nevertheless negative consequences if disposable income is not spent to ensure the agent’s own basic health and survival. One of the possible policy remedies is the design of the tax system. We study an optimal tax system constrained by a no-poverty requirement that forces the social planner to set the tax rates in such a way that all agents achieve a minimum subsistence level of consumption. The policy recommendations are that, relative to non-working time, which is taken as a reference point, (i) marketed goods that are necessary to guarantee the basic needs of a person have to be treated leniently by the tax system; (ii) the status-signalling marketed goods should be treated analogously if they are complements to the basic items but taxed heavily if they are substitutes. It is also argued that the no-poverty requirement may conflict with the usual equity and efficiency requirements and may thus lead to different policy prescriptions.